A Case Report of Inverting Papilloma of Lacrimal Sac - Marie Y. Omana, Elaine; P. Kleiner, Franklin (Journal of Ophthalmic Science, 2019)
Purpose To report a rare case of Inverting Papilloma originating from the Lacrimal Sac in Tertiary Hospital. Method Case report. Results Inverting papilloma is uncommon in lacrimal sac. More often presents in Maxillary sinus, Ethmoid sinus and lateral wall of nasal cavity. This case of 69 years old, Filipino male, who presented with a two-year history of gradually enlarging left medial canthal mass, and tearing. There were no ophthalmoplegia, visual disturbances, proptosis or pain but there was globe displacement superolaterally. Other ophthalmologic examinations were unremarkable at that time of examination. Orbital CT-scan revealed: Heterogenously enhancing mass extending to ipsilateral nasolacrimal canal and nasal cavity causing mass effect. There was note of a suspicious area of hyperostosis. Patient was referred to the Department of Otolaryngology Head and Neck Surgery for co-management. Punch biopsy was done and histopathology revealed Inverting papilloma. Combined surgical management of anterior Maxillectomy via lateral Rhinotomy approach and Dacryocystectomy was done. Intraoperatively, there was note of adhesions to bone in the area of the Lacrimal Sac corresponding to the area of hyperostosis on CT-scan. Post-operative recovery was unremarkable with unchanged visual acuity and extraocular muscle movement. Conclusions This is a case of an inverting papilloma involving the lacrimal sac and nasolacrimal duct that was managed with combined anterior maxillectomy via Lateral Rhinotomy approach and dacryocystectomy for complete resection. We recommended complete resection of the tumor to minimize recurrence. Origin in the Lacrimal Sac area was confirmed by intraoperative findings which correlated with CT- scan findings.
Keywords: Inverting Papilloma; Lacrimal Sac; Dacryocysectomy